Röjning på snö och röjning på barmark : effekter på produktivitet och kvarvarande bestånd - Sahlén, Johanna (SLU/Dept. of Silviculture, 2005)
Approximately 4000-5000 hectares, of SCA´s forest land area in Västerbotten, are in need of pre-commercial thinning (PCT) every year. Within the management district, the areas annually treated with PCT must increase, in order to decrease the area with an urgent need for PCT. This can be done by employing more forest workers or entrepreneurs, by mechanized PCT or by an extended season for PCT. Positive experiences from a private forest owner, who started to carry out PCT when the first snow came and then continued for several months, gave an idea to investigate the possibilities to prolong the season of PCT.